2021
DOI: 10.21608/ejchem.2021.98412.4583
|View full text |Cite
|
Sign up to set email alerts
|

Sweet lupin and whey protein concentrate as supplementants to utilize in semi–hard biscuit and its chemical properties

Abstract: This study aimed to supplement soft wheat flour with different levels of sweet lupin powder and/or whey protein concentrate for producing a semi hard sweet biscuit as a functional product and their effects on the chemical and physical properties of produced biscuit were carried out. The results indicate that lupin and whey protein had 3.94 and 7.5 times higher than those of wheat flour. Fat content was higher in lupin with 2 and 4 folds compared with wheat flour, respectively. Lupin had higher ash content with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 1 publication
(1 reference statement)
0
12
0
Order By: Relevance
“…), followed by Europe which comfortably occupies second place (32.1%, 396 k ha), then Africa (5.4%, 66 k ha), with America having close data (4.6%, 57 k ha); in last place is Asia (<1%, 108 ha). From the geographical point of view, it is possible to group the included articles by origin continents: Europe [ 50 , 51 , 53 , 55 , 59 , 63 , 70 , 72 , 73 , 75 ], South America [ 54 , 58 , 61 , 66 ], Asia [ 47 , 56 , 60 , 64 , 65 , 68 , 69 , 74 , 77 , 78 ], Africa [ 49 , 52 , 62 , 67 , 71 , 76 , 79 ] and Oceania [ 48 , 57 ]. This grouping revealed that Europe and Asia are, for now, the leading promoters of these novel food products, and Africa also reports many studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), followed by Europe which comfortably occupies second place (32.1%, 396 k ha), then Africa (5.4%, 66 k ha), with America having close data (4.6%, 57 k ha); in last place is Asia (<1%, 108 ha). From the geographical point of view, it is possible to group the included articles by origin continents: Europe [ 50 , 51 , 53 , 55 , 59 , 63 , 70 , 72 , 73 , 75 ], South America [ 54 , 58 , 61 , 66 ], Asia [ 47 , 56 , 60 , 64 , 65 , 68 , 69 , 74 , 77 , 78 ], Africa [ 49 , 52 , 62 , 67 , 71 , 76 , 79 ] and Oceania [ 48 , 57 ]. This grouping revealed that Europe and Asia are, for now, the leading promoters of these novel food products, and Africa also reports many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another relation based on the lupin species used when discriminated is possible by comparing its country of acquisition: Albus [ 47 , 49 , 52 , 53 , 59 , 62 , 64 , 65 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ], Angustifolius [ 48 , 51 , 55 , 57 , 67 , 75 ], Mutabilis [ 54 , 61 , 66 ] and Luteus [ 58 ]. Lupinus albus is commonly used in Europe, Asia and Africa, with the highest appearance rates in the selected studies, followed by Lupinus angustifolius in Oceania.…”
Section: Discussionmentioning
confidence: 99%
“…Lupins ( Lupinus albus L.) are distinguished by their high-quality protein and dietary fiber contents, which are associated with cholesterol-lowering activity. Their seeds are enriched with high levels of total unsaturated fatty acids and contain vitamins such as thiamine, niacin, riboflavin, and tocopherols, as well as minerals including iron, zinc, and manganese [ 41 ]. When processed into flour and protein isolates, lupins are rich in antioxidants like polyphenolic tannins and flavonoids [ 52 ].…”
Section: Nutritional Value Of Underutilized Grains As the Basis For T...mentioning
confidence: 99%
“…When compared with soybean and other legumes, lupins have lower levels of anti-nutritional components such as phytate and saponins. Besides, the amounts of lysine, isoleucine, leucine, phenylalanine, and tyrosine in lupin are in the optimal range of reference protein for adults according to the Food and Agricultural Organization (FAO) standards [ 41 ].…”
Section: Nutritional Value Of Underutilized Grains As the Basis For T...mentioning
confidence: 99%
See 1 more Smart Citation